2012
DOI: 10.4025/actascibiolsci.v34i3.8956
|View full text |Cite
|
Sign up to set email alerts
|

Histology of the digestive tract of Satanoperca pappaterra (Osteichthyes, Cichlidae)

Abstract: ABSTRACT. This study aimed to locate, describe and characterize the esophagus, stomach and intestine of Satanoperca pappaterra using histological techniques. The species presents detritivore-invertivore feeding habit and is widely distributed in Neotropical continental waters. The esophagus is short, the stomach is small with saccular form and the intestine is long. The histological sections were stained using hematoxylin/eosin and Periodic Acid Schiff. Throughout the digestive tract, the gastric wall is compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The longer villi found in fish fed lower levels of KM (<75%) in the diet indicate higher efficiency in the absorptive process (Da Silva et al, 2012;Caballero et al, 2003). This was evidenced by the better growth performance of fish fed these diets.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The longer villi found in fish fed lower levels of KM (<75%) in the diet indicate higher efficiency in the absorptive process (Da Silva et al, 2012;Caballero et al, 2003). This was evidenced by the better growth performance of fish fed these diets.…”
Section: Discussionmentioning
confidence: 65%
“…This was evidenced by the better growth performance of fish fed these diets. The decrease in villi height resulted in reduced surface area for nutrient absorption (Da Silva et al, 2012); this may also explain the poor condition of the liver. Furthermore, the enterocytes of these fish showed an increase in goblet cell number and microvilli degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…However, the antioxidant defence system is stimulated and connected to response to pathogenic infections in the host. This fact might be related to the CAT levels observed in fish that kept a similar pattern, seen that the animals displayed stable physiological responses in the proportion of ROSs and reactive species of nitrogen (RNSs) (Silva et al., 2012), while not presenting a release of hydrogen peroxide in the process of β‐oxidation.…”
Section: Discussionmentioning
confidence: 84%
“…The decrease in villi height resulted in reduced surface area for nutrient absorption (Da Silva et al, 2012). The longer villi found in fish fed lower levels of sunflower seed meal in the diet indicate a larger surface area and consequently higher efficiency of the intestine during nutrient absorption (Da Silva et al, 2012). This was corroborated by the better growth performance of fish fed with these diets at lower inclusion levels as reported by Adesina et al (2013).…”
Section: Organosomatic Indices C Gariepinus Fed Graded Levels Of Bssmentioning
confidence: 67%
“…This result agrees with that of Hlophe and Moyo (2014) who observed that the intestine histology of C. gariepinus fed diets containing higher moringa leaf meal inclusion levels (>50%) showed significantly shorter villi. The decrease in villi height resulted in reduced surface area for nutrient absorption (Da Silva et al, 2012). The longer villi found in fish fed lower levels of sunflower seed meal in the diet indicate a larger surface area and consequently higher efficiency of the intestine during nutrient absorption (Da Silva et al, 2012).…”
Section: Organosomatic Indices C Gariepinus Fed Graded Levels Of Bssmentioning
confidence: 99%